Network Pharmacology and Integrated Molecular Docking Study on the Mechanism of the Therapeutic Effect of Fangfeng Decoction in Osteoarthritis - Wang, Wenqiao; Li, Min; Si, Hongzong; Jiang, Zehui (Current Pharmaceutical Design, 2023)
Background: At present, there are no effective pharmacologic therapies for attenuating the course of osteoarthritis (OA) in humans and current therapies are geared to mitigating symptoms. Fangfeng decoction (FFD) is a traditional Chinese medicine prescribed for the treatment of OA. In the past, FFD has achieved positive clinical outcomes in alleviating the symptoms of OA in China. However, its mechanism of action has not yet been clarified. Objective: The objective of this study is to investigate and explore the mechanism of FFD and how the compound interacts with the target of OA; network pharmacology and molecular docking methods were applied in this study. Methods: The active components of FFD were screened by Traditional Chinese Medicine Systems Pharmacology (TCMSP) database according to the inclusion criteria as oral bioactivity (OB) ≥ 30% and drug likeness (DL) ≥ 0.18. Then, gene name conversion was performed through the UniProt website. The related target genes of OA were obtained from the Genecards database. Core components, targets, and signaling pathways were obtained through compound-target-pathway (C-T-P) and protein-protein interaction (PPI) networks were built using Cytoscape 3.8.2 software. Matescape database was utilized to get gene ontology (GO) function enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment of gene targets. The interactions of key targets and components were analyzed by molecular docking in Sybyl 2.1 software. Results: A total of 166 potential effective components, 148 FFD-related targets, and 3786 OA-related targets were obtained. Finally, 89 common potential target genes were confirmed. Pathway enrichment results showed that HIF-1 and CAMP signaling pathways were considered key pathways. The screening of core components and targets was achieved through the CTP network. The core targets and active components were obtained according to the CTP network. The molecular docking results showed that quercetin, medicarpin, and wogonin of FFD could bind to NOS2, PTGS2, and AR, respectively. Conclusion: FFD is effective in the treatment of OA. It may be caused by the effective binding of the relevant active components of FFD to the targets of OA.
Keywords: signaling pathway